Origin And Development of Athletics - Odilov Otabek Norboyevich (Genius Journals, 2021)
This article summarizes the origins of athletics. In ancient times, there were competitions in running, jumping, and throwing at large events and ceremonies. Accordingly, this sport was included in the ancient Olympic Games. Modern athletics is also a multi-sport sport that includes the above sports: walking, running, jumping, throwing, and so on.
Keywords: Athletics; competition; wrestling; exercise